1986
DOI: 10.1083/jcb.103.5.1855
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 52-kD calmodulin-binding protein associated with the mitotic spindle apparatus in mammalian cells.

Abstract: Abstract. A pool of 10 calmodulin-binding proteins (CBPs) was isolated from Chinese hamster ovary (CHO) cells via calmodulin (CaM)-Sepharose affinity chromatography. One of these ten isolated CBPs with a molecular mass of 52 kD was also found to be present in isolated CHO cell mitotic spindles. Affinitypurified antibodies generated against this pool of isolated CBPs recognize a single 52-kD protein in isolated CHO cell mitotic spindles by immunoblot analysis. Immunofluorescence examination of CHO, 3T3, NRK, PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…This suggests that anaphase would not require a motor, but only controlled depolymerization at the plus end of microtubules of the kinetochor¢ fibers, consistent with a recently proposed model [28], More recent experimental results obtained with permeabilized cells models favor the idea that ATP would be required at anaphase for microtubule disassembly and not as a substrate for a motor exerting poleward forces on the chromosomes [84]. Other results have shown that calmodulin is associated with the mitotic spindle indirectly through binding to a calmodulin.binding protein [7], and that the free Ca 2+ concentration changes during mitosis [72]. Furthermore, mitosis has been shown to be inhibited, in sand dollar embryos, by microinjection of antiho-2+ dies directed against the muscle ~Ca pump [83].…”
Section: Mitosissupporting
confidence: 77%
“…This suggests that anaphase would not require a motor, but only controlled depolymerization at the plus end of microtubules of the kinetochor¢ fibers, consistent with a recently proposed model [28], More recent experimental results obtained with permeabilized cells models favor the idea that ATP would be required at anaphase for microtubule disassembly and not as a substrate for a motor exerting poleward forces on the chromosomes [84]. Other results have shown that calmodulin is associated with the mitotic spindle indirectly through binding to a calmodulin.binding protein [7], and that the free Ca 2+ concentration changes during mitosis [72]. Furthermore, mitosis has been shown to be inhibited, in sand dollar embryos, by microinjection of antiho-2+ dies directed against the muscle ~Ca pump [83].…”
Section: Mitosissupporting
confidence: 77%
“…This difference was previously noted and reported in various mitotic cells (1,2,7,19,23,24), although the exogenous calmodulin can bind to tubulin (12,13) or to microtubules (4,5) in the mitotic apparatus. The accumulation of calmodulin in the polar regions of the spindle can be explained by the preferential binding of calmodulin to some calmodulin-binding proteins specifically localized in the polar regions of the spindle, as shown in mammalian cells (2).…”
Section: Discussionmentioning
confidence: 45%
“…That pp50 is a Ca2+/CaM binding MAP therefore suggests its involvement. It is noteworthy that a Ca2+/CaM binding protein with an apparent molecular mass similar to pp50's may also be an animal MAP that mediates CaM's association with mitotic spindle MTs (Brady et al, 1986).…”
Section: Localizations Of Tubulin Cam and Ef-1a In Plantsmentioning
confidence: 99%